The CDKN2A/p16INK4a 5′UTR sequence and translational regulation: impact of novel variants predisposing to melanoma. (17th December 2015) - Andreotti, Virginia; Bisio, Alessandra; Bressac‐de Paillerets, Brigitte; Harland, Mark; Cabaret, Odile; Newton‐Bishop, Julia; Pastorino, Lorenza; Bruno, William; Bertorelli, Roberto; De Sanctis, Veronica; Provenzani, Alessandro; Menin, Chiara; et al.
Summary: Many variants of uncertain functional significance in cancer susceptibility genes lie in regulatory regions, and clarifying their association with disease risk poses significant challenges. We studied 17 germline variants (nine of which were novel) in the CDKN2A 5′UTR with independent approaches, which included mono and bicistronic reporter assays, Western blot of endogenous protein, and allelic representation after polysomal profiling to investigate their impact on CDKN2A mRNA translation regulation. Two of the novel variants (c.‐27del23, c.‐93‐91delAGG) were classified as causal mutations (score ≥3), along with the c.‐21C>T, c.‐34G>T, and c.‐56G>T, which had already been studied by a subset of assays. The novel c.‐42T>A as well as the previously described c.‐67G>C were classified as potential mutations (score 1 or 2). The remaining variants (c.‐14C>T, c.‐20A>G, c.‐25C>T+c.‐180G>A, c.‐30G>A, c.‐40C>T, c.‐45G>A, c.‐59C>G, c.‐87T>A, c.‐252A>T) were classified as neutral (score 0). In conclusion, we found evidence that nearly half of the variants found in this region had a negative impact on CDKN2A mRNA translation, supporting the hypothesis that 5′UTR can act as a cellular Internal Ribosome Entry Site (IRES) to modulate p16 INK 4a translation.